Much laughter, little siso? The moment of fun and the uses of social (in) visibility of the bodies for school-age children in ATL - Rita Maria Ribeiro Gonzalez (Universidade Federal de Santa Catarina, 2008)
The argument that children, individually and collectively, are competent social actors in social practices that make their bodies to express themselves and say strategically in the face of power and knowledge between themselves and adults, is based on the sociology of childhood, and Body of Leisure and is based on participant observation of a group of children attending a PTA urbano. The analysis of moments of "fun" - marked by expressions and non-verbal body verbal, exciting and exacerbated, who poured in (s) group (s) of children and create unusual situations, comic and bizarre -, to intersect both the adult-child interaction between them on a daily basis of ATL, reveals i) facets crop of peer-laden children's senses and opted for a significant expression of easily understood, because shared among members of the group ii) other modes of interpretation of collective child who is critical of the functioning of the ATL, iii) their difficulties for adults interpret the "fun" in terms of children, iv) the participation of children in institutions where the social educative and recreational exacerbated extreme visibility modes are privileged to claim a free time that can be yours.